Gender differences in teachers' occupational accidents. - Rey-Merchán, María del Carmen; López-Arquillos, Antonio (Routledge Taylor&Francis, 2021)
The authors stated that the main objective of the current research is to analyze the relationship between the gender of injured teachers and independent variables, such as age, place of the accident, absence days, and severity of the injury, to improve women’s occupational health and safety. Teachers’ accidents recorded in Spain (N = 136,702) from 2003 through 2018 were analyzed by calculating their incidence rates, using statistical tools for independent samples. Gender differences were found in some of the variables studied. Women were more likely to suffer an occupational accident. Compensation per lost working day was found to be statistically lower for women, but no differences based on gender were found in the absence days due to occupational accidents suffered by teachers. The salary gap should be addressed to avoid gender economic discrimination among injured teachers. Preventive strategies should be developed to mitigate the negative difference caused by gender variables
Keywords: Igualdad de género; Profesores - Accidentes; Gender; Occupational; Accident